GROUP KOHESIVITAS DAN GAYA KEPEMIMPINAN PEMODERASI HUBUNGAN PARTISIPASI ANGGARAN DAN SENJANGAN ANGGARAN - Isma Coryanata (UNIB Press, 2017)
This study examined influence of group cohesiveness and the role of leadership style on the relationship between budgetary participation and budgetary slack. The samples in this study using purposive sampling. The subjects of this study are middle and lower manager in local govermment institutions including section /departement/sub-section head, under the municipality and regencies in the city government of Bengkulu were amounted to 63 respondents. Hypothesis are tasted empirically used regression. The result of study indicated that, first, budgetary participation influences to budgetary slack. Second, group cohesiveness as moderating variable in the relation of budgetary participation with budgetary slack. Third, the role of leadership syle as moderating variable in the relation of budgetary participation with budgetary slack. Therefore this study sported anothetr studies before.Keywords: budgetary participation, budgetary slack, group cohesiveness, the role of leadership style